POWER LAW DISTRIBUTION AS A COMPONENT OF THE VERTEX DEGREE DISTRIBUTION ON A SOCIAL UNIVERSITY NETWORK COURSE - Gjermeni, Orgeta (European Scientific Journal, ESJ, 2015)
The aim of this paper is to analyze a collection of data gathered from surveys held every three weeks in a Spring Course of the Economic Faculty in the University “Ismail Qemali”of Vlora, Albania. The data set for each student also contains the names of other students through which he/she have a “social relationship”. This social relationship includes frequent communications, discussions on exercise solutions, and sitting usually close to each other in the class. We have constructed four social simple graphs and have analyzed them focusing only on degrees. In addition, we fit discrete power law degree distribution on the tail and their evolution through time. In analyzing the data, we employed the R platform.